Preterm milk as a source of protein for low birthweight infants. - Lucas, A (1984)
A total of 588 samples of 24 hour collections of preterm milk obtained during the first month of lactation from 58 mothers of low birthweight infants have been analysed for total nitrogen content. In addition to the expected decline in milk protein content (total nitrogen X 6 X 38) seen with postnatal age, a strong negative correlation between milk protein and milk volume output has been shown. Thus, the greater the volume produced, the smaller the chance that preterm milk contains a sufficiently high protein concentration to meet the calculated requirements of low birthweight infants (given the constraints on the infant's volume intake). Postnatal age and the infant's body weight are identified as additional factors which influence the likelihood that theoretical protein needs will be met. It is speculated that the high protein content seen in preterm milk may not necessarily reflect a unique secretory ability of the mammary gland in mothers delivering preterm but may relate more to the low volume of milk produced by many donors.